2007
DOI: 10.1645/ge-973r.1
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasites in an Urban Population of Big Brown Bats (Eptesicus Fuscus) in Colorado

Abstract: Ectoparasites of an urban population of big brown bats (Eptesicus fuscus) in Fort Collins, Colorado, were investigated during summers 2002, 2003, and 2004. Eleven species of ectoparasites were found (the macronyssid mite Steatonyssus occidentalis, the wing mite Spinturnix bakeri, the myobiid mites Acanthophthirius caudata and Pteracarus aculeus, the chirodiscid mite Alabidocarpus eptesicus, the demodicid mite Demodex sp., the chigger Leptotrombidium myotis, the soft tick Carios kelleyi, the batfly Basilia forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Pearce and O'Shea (2007) found that large adult brown bats had more ectoparasites than volant juveniles for most of the species analysed. Mite load and the condition of the bats were negatively correlated in a study by Lourenço and Palmeirim (2007) and the information available suggests that this may be due to an effect of parasitism.…”
Section: Discussionmentioning
confidence: 85%
“…Pearce and O'Shea (2007) found that large adult brown bats had more ectoparasites than volant juveniles for most of the species analysed. Mite load and the condition of the bats were negatively correlated in a study by Lourenço and Palmeirim (2007) and the information available suggests that this may be due to an effect of parasitism.…”
Section: Discussionmentioning
confidence: 85%
“…At least one species of the genus, E. fuscus (Palisot de Beauvois), occurs today in Hispaniola (Rodríguez-Durán & Kunz, 2001). Extant species of Eptesicus are parasitised by nycteribiid bat flies of the genus Basilia Miranda Ribeiro, 1903 in Panama, Venezuela and Colorado (Guimarães, 1966;Pearce & O'Shea, 2007). Another possible host candidate for Enischnomyia stegosoma is a tree-roosting red bat of the genus Lasiurus H. Allen.…”
Section: Discussionmentioning
confidence: 99%
“…We used an analysis of relative variable importance (Burnam andAnderson 2002, Neubaum et al 2006) using Akaike's Information Criteria corrected for sample size (AICc) to determine the relative importance of these variables to the seroprevalence of RVNA in big brown bats. Our objectives in this analysis did not include testing of hypotheses about factors influencing ectoparasite intensities, which are explored by Pearce and O'Shea (2007), but we focus, instead, on factors influencing the presence of RVNA.…”
Section: Introductionmentioning
confidence: 99%